Удосконалення методики визначення рівня безпеки на автомобільних дорогах - Птиця, Геннадій (Видавництво Львівської політехніки, 2013)
Identification and analysis of road safety is the first step in the management of safety and is crucial in the development of measures directed to prevent and reduce the number of road traffic accidents. The given study substantiates the need for improving the determination of safety level indexes of traffic on public roads, and the peculiarities as well as limitations concerning practical application of the existing methods used for determining the basic safety parameters are specified. An approach to improving the existing techniques using the methods of multivariate statistical analysis, the methods of cluster analysis, and the factor analysis methods for streamlining and reduction of parameters taken into account by the existing methods is proposed. The scheme of improvement phases according to the selected criteria is drawn up, and each criterion is consistently described. The results of theoretical research on reducing the number of parameters that are investigated at the expense of switching from individual accident coefficient to latent ones are offered.
Keywords: безпека дорожнього руху; рівень безпеки; удосконалення; підсумковий коефіцієнт аварійності; латентні фактори